Cashew : Export Challenges Ahead - Patil, Parashram Jakappa (AMC Indian Journal of Entrepreneurship, 2020)
For the first time after independence, India has framed the first agriculture export policy through which the government wants to double agriculture export and double farmers income by 2022. Cashew is the most important product in India’s agriculture export basket which has tremendous export potential. India is one of the largest cashew exporters in the world. In recent times, cashew export sector is facing various challenges that threaten India’s position in the world cashew market.